THE AL-DIN CONCEPT IN ISLAMIC ECONOMIC - Basmaida Waty Tambusay (Proceeding International Seminar of Islamic Studies, 2023)
The concept of Ad Din covers all aspects of life, including the economy. In the context of Islamic economics, Ad Din refers to Islamic principles that govern the economic behavior of individuals and society. Ad Din principles in Islamic economics include concepts such as ownership, production, distribution, and consumption. In Ad Din, ownership is viewed as a divine mandate from Allah SWT that must be used wisely.Therefore, Islamic economics encourages ownership based on the principles of justice, balance, and social responsibility. Production in Ad Din must be done in a good and correct way. Therefore, concepts such as balance, sustainability, and quality are considered very important in production in an Islamic economy. Distribution in Ad Din must be done in a fair and equitable manner, and everyone must have an equal opportunity to acquire wealth. Consumption in Ad Din must also be done in a good and correct way. Excessive and wasteful consumption is considered not beneficial to individuals or society. Therefore, Islamic economics encourages consumption based on important needs and interests. In conclusion, the concept of Ad Din in Islamic economics provides a strong moral foundation for individual and societal economic behavior. This concept governs ownership, production, distribution, and consumption and promotes the principles of fairness, balance, sustainability, and social responsibility.